Effect of Additives on the Yield and Quality of Palm Oil: Additives Effect on the Yield and Quality of Palm Oil (Biological Sciences - PJSIR, 2009)
In the study of the effect of additives namely Manihot esculenta Crantz, (cassava), Erythrina senegalensis (ukwa) and Oxytenanthera species (bamboo) leaves, on the yield and quality of traditionally processed palm oil, the raw leaves were found to contain some anti-nutrients like tannins, oxalates, trypsin inhibitors, alkaloids and phytic acid at tolerable levels. The additives increased the yield from 300 ml (of the control) to 450 ml with a standard deviation of  60.6 ml. The peroxide value was in the range of 0.4-1.0 meq/kg, free fatty acid varied between 0.847-1.12 mg KOH/g, iodine value between 51.01-52.54, saponification value between 7.84-93.97 KOH/g of oil and moisture content, between 1.4-1.8%. Analysis of variance (ANOVA) showed significant differences, (P0.05) in the moisture contents, free fatty acid, specific gravity, smoke point, flash point and fire points. The standard deviation results revealed that the palm oil produced using ukwa leaf differed from the others in terms of smoke, flash, and fire points. Cassava leaves was the best of the studied additives in terms of yield with the physical properties comparing favourably with the control. Chemical properties were similar to the control with the exception of the saponification value.